Educational Robotics, advances and challenges for integrated high school and technical education - Afecto, Romeu; Moretti, Andressa Algayer da Silva [UNESP]; Teixeira, Lucimara de Sousa (Univ Nove De Julho-uninove, 2024)
This article presents an experience report on the implementation of educational robotics in a public high school integrated with technical education, Etec Albert Einstein, which belongs to the public network of technical schools in the State of S & atilde;o Paulo, administered by the Paula Souza State Education Center, linked to the State Department of Science and Technology. The experience is characterized as an excerpt from the doctoral thesis defended at Universidade Nove de J & uacute;lio - UNINOVE and funded by FAPESP, which addresses the advances, challenges and impact of educational robotics on the development of skills and competencies of students in the Mtec courses in Systems Development and Electronics. The study was conducted through a qualitative approach and case study, involving the participation of managers, teachers and students. The results indicate that educational robotics, integrated with the project-based learning methodology and the STEAM approach, contributes significantly to the constructivist learning of students, promoting interdisciplinarity and innovation.
Keywords: educational robotics; STEAM; project-based learning; technical high school; public education